Glass formation in the Sb2O3-SbPO4-WO3 system - Franco, Douglas Faza; Fares, Hassen; de Souza, Antônio Eduardo; Santagneli, Silvia Helena; Nalin, Marcelo (Eclética Química, 2017)
Glasses in the ternary system (Sb2O3)(0.6-x)(SbPO4)(0.4)(WO3)(x), with composition 0.1 £ x £ 0.5 were studied. The structural changes due to the replacement of Sb2O3 by WO3 have been investigated. It was found that the incorporation of WO3 enhances the thermal stability of the glasses against devitrification when compared to the binary Sb2O3(0.6) - SbPO4(0.4) composition. The connectivity of the network increases with WO3 content which is consistent with the high values of the glass transition temperature. Raman studies suggest that WO3 incorporation breaks the primary network, constituted by antimony oxide, while a second network containing WO6 octahedral units is built up. Thermal and structural properties were evaluated by differential scanning calorimetry, infrared and Raman spectroscopies, 31P Magic Angle Spinning NMR and X-ray absorption near edge structure (XANES) at L1 and L3 edges of Sb and L1 edge of W atoms.